CHARACTERISTICS OF THE MEANS AND METHODS USED IN SOCCER TRAINING - Yang,Bin (2023)
ABSTRACT Introduction The correct understanding and implementation of the tasks set by the coach for the player are achieved through a wide variety of training sessions. To date, the question of training effectiveness and the preparation of professional soccer players for matches has not been sufficiently studied. Objective Study the means and methods used in soccer training. By comparison, find out which method is most effective in achieving a positive result during the game and maintaining the players’ health. Methods The study used mathematical and physical methods and comparative analysis. In the study, the main training methods in a team were considered. A comparative analysis was made between two types of individual soccer players’ training to improve physical and technical parameters. Result We established which parameters influence the choice of the training scheme. The effectiveness of both training systems is proven by the statistical indicators of soccer players who train according to these methods. Conclusion The effectiveness of the training methodology chosen by a soccer player depends on his initial physical abilities and professional skills. The study’s practical significance is determined by the fact that the proposed methods can be used in training professional athletes. Evidence level II; Therapeutic studies - outcomes research.